Testing a relational spirituality model of psychotherapy clients' preferences and functioning. Issue 1 (2nd January 2022) - Sandage, Steven J.; Jankowski, Peter J.; Paine, David R.; Exline, Julie J.; Ruffing, Elizabeth G.; Rupert, David; Stavros, George S.; Bronstein, Miriam
ABSTRACT: This study tested hypotheses about client preferences and functioning based on a relational spirituality model of psychotherapy in a sample (N = 101) of adult clients at a community mental health center in the northeastern United States. Most clients wanted to engage spiritual, religious, and existential issues in treatment and this preference was positively related to both spiritual/religious commitment and questing. Clients' ratings of therapist diversity sensitivity were associated with ratings of treatment progress over and above the working alliance. Client spiritual well-being and spiritual struggles predicted their psychosocial functioning over and above mental health symptoms. Clinical and research implications are discussed.